Assessing the Feasibility of Public-Private Partnerships in Health in the Philippines - Eduardo P. Banzon; J.A. Lucero; B.L. Ho; M.E. Puyat; P.A. Factor; F.J. Young (Philippine Institute for Development Studies (PIDS), 2014)
The government has decided to utilize the public-private partnership (PPP) program to help improve access to quality hospitals and health care facilities. This paper looks into the feasibility of implementing PPPs in the health sector. Review of literature, key informant interviews, and focus group discussions were conducted for the study. The Philippine hospital system was reviewed using five performance criteria, namely, improved health care access, equity, and quality, operating with maximum efficiency, and ensuring sustainability followed by the development of an assessment framework; the application of the said framework; and policy and program implementation recommendations for health PPPs.In order to improve the feasibility of PPPs in the health sector, it is recommended that the government use public-private investment partnerships as the definition for health PPPs, encourage public policy discussions on PPP and its relation to socioeconomic development, and develop a comprehensive communications program for PPPs. It needs to rectify shortcomings in previous PPPs and ensure absolute transparency and accountability in the entire PPP process. There is a need to amend the legal framework to ensure coherence of health PPPs. It should conduct joint capacity-building initiatives and develop and enforce an evidence-based decisionmaking process for PPPs. It needs to strengthen implementation of monitoring and evaluation and utilize the health system indicators in evaluation of PPPs. Finally, it should ensure universal PhilHealth membership to attract private sector.
Keywords: 330; Philippines; health; public-private partnership (PPP); public-private investment partnerships; public-private interactions